KAT2A/KAT2B-targeted acetylome reveals a role for PLK4 acetylation in preventing centrosome amplification - Marjorie Fournier (Nature Portfolio, 2016)
The acetyltransferases KAT2A and KAT2B are essential regulators of transcription, cell cycle progression and DNA repair. Here the authors describe a KAT2A/2B-dependent acetylome, and show that acetylation of the protein kinase PLK4 contributes to the regulation of centrosome number.